PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN TERHADAP KINERJA MANAJERIAL DENGAN GAYA KEPEMIMPINAN, MOTIVASI KERJA, KOMITMEN ORGANISASI, DAN BUDAYA ORGANISASI, SEBAGAI VARIABEL MODERATING PADA PERBANKAN DI PEKANBARU - Rika Mayasari; Raja Adri Satriawan; Rofika - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
Manager participation in the preparation of the budget will lead the initiative for them to develop ideas and information, enhance solidarity so as to create commitment among managers that can be managerial performance benchmarks. Influence of budget participation on managerial performance is influenced by leadership style, work motivation, organizational commitment, and organizational culture as moderating variable. The population in this study is the manager or manager-level in the bank's main branch office in Pekanbaru. Data used in this study are primary data obtained from the respondents on the questionnaire that deliver. Hypothesis testing is done is Moderated Regression Analysis with SPSS version 20. From these results it can be concluded that the participation budgeting has a significant positive effect on managerial performance. While variable leadership style, work motivation, organizational commitment and high organizational culture will further increase the effect of budget participation on managerial performance.Keywords: Participation budgeting, performance, leadership, work motivation.